2004
DOI: 10.1021/np034066u
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Larvicidal Studies on Stemona curtisii:  Structure of a New Pyrido[1,2-a]azepine Stemona Alkaloid

Abstract: A new pentacyclic Stemona alkaloid, stemocurtisinol (3), with a pyrido[1,2-a]azepine A,B-ring system, and the known pyrrolo[1,2-a]azepine alkaloid oxyprotostemonine (4) have been isolated from a root extract of S. curtisii. The structure and relative stereochemistry of stemocurtisinol was determined by spectral data interpretation and X-ray crystallography. This compound is a diastereoisomer of oxystemokerrin and has the opposite configuration at C-4 and C-19. The individual alkaloid components showed signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 8 publications
2
58
0
Order By: Relevance
“…Although no similar investigation was found in the literature for oxoaporphine alkaloids, some nitrogenated compounds have been presented as promising larvicides. [19][20][21][22] The chemical composition of the essential oils from the leaves and stems of R. leptopetala showed quantitative and qualitative variation. The leaf oil consisted mainly of oxygenated monoterpenes (47.7%), with linalool and 1,8-cineole as the major compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Although no similar investigation was found in the literature for oxoaporphine alkaloids, some nitrogenated compounds have been presented as promising larvicides. [19][20][21][22] The chemical composition of the essential oils from the leaves and stems of R. leptopetala showed quantitative and qualitative variation. The leaf oil consisted mainly of oxygenated monoterpenes (47.7%), with linalool and 1,8-cineole as the major compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the pure alkaloids derived from the extracts of the leaves and roots of Stemona species have been shown to have significant antitussive activity in guinea pigs after cough induction [15] as well as insect toxicity, antifeedant, and repellent activities [13,16]. We found that compounds 11, 12, and 14 had significant larvicidal activity on malaria-carrying mosquito larvae (Anopheles minimus HO) [14].…”
Section: Stemona Alkaloidsmentioning
confidence: 81%
“…The pyrrolo[1,2-a]azepine (5,7-bicyclic A,B-ring system) nucleus is common to all compounds in these groups (e.g., croomine 10). In 2003, we [12] and then Greger [13] reported the structures of Stemona alkaloids with a pyrido[1,2-a]azepine A,B-ring system (that is, a 6,7-bicyclic A,B-ring system), including stemocurtisine 11 and oxystemokerrin 12, and in 2004 we disclosed the structure of another pyrido[1,2-a]azepine Stemona alkaloid, stemocurtisinol 13 [14]. These alkaloids comprise a new and sixth structural group.…”
Section: Stemona Alkaloidsmentioning
confidence: 99%
“…In 2003, we reported the first pyrido[1,2-a]azepine based Stemona alkaloid, stemocurtisine 1 (Scheme 1), which was isolated from the roots of Stemona curtisii found in Trang Province, Thailand [Mungkornasawakul et al, 2003]. Other Stemona alkaloids with a pyrido[1,2-a]azepine structure were later reported by us [Mungkornasawakul et al, 2004;Pyne et al, 2007]], Greger [Kaltenegger et al, 2003] and Ye [Wang et al, 2007]. Pilli has classified these natural products as Stemocurtisine-type alkaloids [Pilli et al, 2010].…”
Section: Introductionmentioning
confidence: 99%